2020
DOI: 10.1371/journal.pone.0234199
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a perioperative oral opioid substitution protocol during the nationwide intravenous opioid shortage: A single center, interrupted time series with segmented regression analysis

Abstract: Introduction To mitigate the recent nationwide shortage of intravenous opioids, we developed a standardized perioperative oral opioid guideline anchored with appropriate use of nonopioid analgesia, neuraxial and loco-regional techniques. We hypothesize that adoption of this new guideline was associated with: 1) equivalent patient reported pain scores in the postanesthesia care unit (PACU); and 2) equivalent total opioid use (oral and parenteral) during the perioperative period. Methods Cases performed from Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…One potential cost savings is the use of oral analgesics compared to IV medications. During an institutional opioid shortage, Salajegheh et al 42 compared the effectiveness of oral opioids compared to IV and found no difference in patient pain scores. Moreover, they reported that overall opioid use during this time decreased.…”
Section: Conmentioning
confidence: 99%
“…One potential cost savings is the use of oral analgesics compared to IV medications. During an institutional opioid shortage, Salajegheh et al 42 compared the effectiveness of oral opioids compared to IV and found no difference in patient pain scores. Moreover, they reported that overall opioid use during this time decreased.…”
Section: Conmentioning
confidence: 99%
“…8 In contrast, the reported impact of injectable opioid shortages in the pediatric, emergency department, and intraoperative/immediate postoperative settings have been less detrimental and were in fact associated with reduced opioid use and no worsening of pain. 7,9,10 The differences in findings may reflect not only the practice setting, but also the patient samples, outcomes evaluated, and strategies used at each facility to manage the drug product shortages. Because injectable opioid shortages are likely to continue, further research on how best to manage the impact is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Use of these alternative approaches has been shown to decrease total opioid doses, reduce pain scores, and reduce hospital length of stay. [5][6][7] Despite the concerns over injectable opioid shortages and reported impacts in some settings, [8][9][10] little is known about how these shortages affect outcomes for adult patients requiring acute pain management while hospitalized postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Oral pain management prior to surgery can effectively reduce postoperative pain [9]. During a nationwide IV opioid shortage, Salajegheh et al compared the effect of oral opioids administered compared to intravenous opioids on patient outcomes at our institution [10]. The results showed no difference in pain scores between the two groups, despite oral opioids being used more commonly than IV.…”
Section: Introductionmentioning
confidence: 99%